Mental health and life-course shocks in a low-income country: Evidence from Malawi - Ally Scheve; Chiwoza Bandawe; Hans-Peter Kohler; Iliana V. Kohler (Elsevier, 2022)
Economic insecurity has been widely hypothesized to be an important determinant of mental health, but this relationship has not been well-documented in low-income countries. Using data from the Mature Adults Cohort of the Malawi Longitudinal Study of Families and Health (MLSFH-MAC), we investigate the association of negative economic shocks with mental health outcomes such as depression and anxiety among adults aged 45+ years living in a low-income country. Using fixed effects estimates that control for time-invariant unobserved individual heterogeneity, we find that increased economic instability caused by events such as death of a family member, yield loss, or income loss is positively associated with worse mental health outcomes as measured by the PHQ-9 and GAD-7 instruments. Our results suggest that costly economic events are a key component to worsening mental health in settings characterized by pervasive poverty and underscore the importance of mental health as a public health and development target.